Endovascular treatment of traumatic aortic rupture using iliac extension stent-grafts in patients with small aortic diameters. (17th January 2022) - Schibilsky, David; Kondov, Stoyan; Gottardi, Roman; Kreibich, Maximilian; Lehane, Cornelius; Berger, Tim; Beyersdorf, Friedhelm; Siepe, Matthias; Czerny, Martin; Rylski, Bartosz
Abstract: OBJECTIVES: To evaluate outcomes after thoracic endovascular aortic repair in young patients sustaining traumatic blunt aortic injury (BAI) using iliac extension stent-grafts because of small aortic diameters measuring <24 mm. METHODS: Retrospective analysis regarding clinical presentation, trauma management, endovascular techniques and outcome of patients with a small descending aorta involving an iliac extension stent-graft to treat traumatic BAI. RESULTS: Among 48 patients who suffered a BAI and underwent thoracic endovascular aortic repair, 7 received iliac extension stent-grafts. They were 27.4/[standard deviation (SD): −13.1] years old and 6 out of 7 were male. The iliac extension stent-graft was used as distal stent-graft, and a thoracic stent-graft was used in most patients as proximal extension. We achieved overall technical success in all patients during a procedure lasting 92.6 (SD: 54.9) min. One patient died 2 days after the endovascular procedure of hypoxic brain injury, and another died after 17 days of liver failure. That patient had also suffered a spinal cord injury following the procedure, as the stent-graft had been deployed in Ishimaru Zone 2, and the carotid to subclavian bypass had to be omitted because of his critical condition. Control computed tomographic angiographs was available in 6 patients after 7.7 (SD: 5.1) days and showed no endoleak. The surviving patients were discharged after 18.4 (SD: 13.4) days. CONCLUSIONS: Treating traumatic BAI using iliac extension stent-grafts in young patients with small aortic diameters is feasible. We observed no mortality caused by the BAI or related to endovascular therapy within this small patient cohort. Abstract : Blunt aortic injury (BAI) can be a life-threatening result of severe trauma, especially deceleration trauma often resulting from high-speed traffic accidents [1, 2].